Proses Penerbitan Billing Ship Sanitation Control Excamption Certificate Melalui Sistem Indonesia National Single Window (INSW) Sinkarkes pada Kapal Sea Win III Oleh PT. Putra Samudera Inti Batam - Jesika Avilla Br Sembiring; Syarifur Ridho; Masringgit Marwiyah Nst (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to find out how the process of issuing a billing ship sanitation control exemption certificate through the Indonesian National Single Window (INSW) syncarceral system on the Sea Win III ship by PT. Putra Samudera Inti Batam. The method used in collecting and writing this paper uses the field research method in library research. The purpose and writing of this paper is to find out the flow of making a billing ship sanitation control exclusion certificate when you want to extend an expired Ship Sanitation Control Excamption Certificate (SSCEC). In accordance with applicable provisions, ships can sail if the certificate is still valid and the ship is declared healthy or free from pests or pollution, and in accordance with the route, ships entering Batam port must have complete documents and have a yellow flag which is one of the proofs that states The ship is healthy from the Port Health Quarantine office. The agent must have good relationships with the relevant agencies in Batam, so that the ship's arrival and departure process can run smoothly so that there are no obstacles in the system or in the field and runs in accordance with government regulations.